KEBIJAKAN TRANSFER SENJATA IRAN KE KAWASAN TIMUR TENGAH DAN AFRIKA (Studi Kasus: Penolakan Iran Terhadap Traktat Perdagangan Senjata Tahun 2013) - Rizqy Riandi; Ahmad Jamaan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research reveals Iran’s motivation on the rejection of United Nations Arms Trade Treaty resolution adoption in 2013. This policy related to Iran’s foreign policy towards Middle east and Africa region. The treaty is the first international agreement that offers a comprehensive regulation about international arms transfer wich aimed to restrict arms flows from, to, and through every states which has imposed by embargo sanction, violent conflict and human rights abuses.The reason of the rejection of Arms Trade Treaty by Iran analyzed with realism though and theory of foreign policy. Concept of threat, national interest, national capability, and oppoturnity are factors that formulating a state’s foreign policy objective. This research using state level of analiysis as the focus of inquiry.Iran has a foreign policy objective to accommodating its political, military, and ideological interests toward Middle East and Africa region. The interest implemented in the form of arms transfer to both of regions. Although Iran still importing arms from many countries, but actually Iran has capability to independently producing and transferring its arms to other states. Thus, Iran stand against the Arms Trade Treaty of 2013 because this international instrument will threaten Iran’s arms transfer.Keywords: Africa, Arms Trade Treaty, Arms Transfer, Middle East, Foreign Policy